Impact of different types of entrepreneurial alertness on entrepreneurial opportunities identification - Li, Zhenning; Jiang, Bing; Bi, Shulei; Feng, Jing; Cui, Qianyi (Frontiers in Psychology, 2022)
For the traditional problem of "why some people can find entrepreneurial opportunities ignored by others," this paper constructed a theoretical mechanism model of entrepreneurial alertness on entrepreneurial opportunities identification of new ventures from the perspective of entrepreneurial cognition theory and bricolage theory. Furthermore, this paper deeply discussed the intermediary role of bricolage and the regulatory role of entrepreneurial passion. Results show that:(1) The three dimensions of entrepreneurial alertness (scanning and search, association and connection, and evaluation and judgment) positively affect entrepreneurial opportunities identification. (2) Both selective and parallel bricolage positively affect entrepreneurial opportunities identification. Among them, selective bricolage promotes the effect more significantly. (3) Selective bricolage and parallel bricolage mediate between entrepreneurial alertness and entrepreneurial opportunities identification. (4) Entrepreneurial passion positively moderates the relationship between entrepreneurial bricolage and entrepreneurial opportunities identification. It also positively moderates the mediating role of entrepreneurial bricolage between entrepreneurial alertness and entrepreneurial opportunities identification. The research conclusion opens the "black box" between entrepreneurial alertness and entrepreneurial opportunities identification. It reveals a theoretical pathway for entrepreneurial alertness to drive entrepreneurial opportunities identification from the behavioral perspective of entrepreneurial bricolage.